2002
DOI: 10.1007/s00467-002-0831-4
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic intracardiac thrombus in steroid-sensitive nephrotic syndrome

Abstract: Arterial and venous thrombotic events can lead to severe complications in the nephrotic syndrome, but may remain clinically silent in a substantial proportion of patients. Intracardiac thrombi associated with multiorgan thrombosis have been described in autopsy cases of the earlier literature, but have never been documented in vivo. We here report an asymptomatic intracardiac thrombus in a child with frequently relapsing steroid-sensitive nephrotic syndrome and a ventricular septal defect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…In a large survey including 3,177 children with NS, Egli et al found 1.8% of various thromboembolic complications, including two patients with CSVT, and reported on one of them [14,15]. However, the prevalence of thromboembolism in NS is thought to be underestimated [23,52]. Divekar et al have observed a single case of CSVT among 700 hundred consecutive patients with NS [12].…”
Section: Discussionmentioning
confidence: 96%
“…In a large survey including 3,177 children with NS, Egli et al found 1.8% of various thromboembolic complications, including two patients with CSVT, and reported on one of them [14,15]. However, the prevalence of thromboembolism in NS is thought to be underestimated [23,52]. Divekar et al have observed a single case of CSVT among 700 hundred consecutive patients with NS [12].…”
Section: Discussionmentioning
confidence: 96%
“…In most reported cases of thromboembolic events in NS, treatment with high-dose heparin with or without thrombolytic agents, has been found to be effective in resolution of thrombus. 4) So for these patients, long-term anticoagulant therapy is particularly important.…”
Section: Discussionmentioning
confidence: 99%
“…Intracardiac location of thrombus in NS patients is extremely rare (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). To date, intracardiac thrombi have been reported in 15 patients (3, 6-18); in 5 adults (7-11) and 10 children (3, 6, 12-18).…”
Section: Pathophysiology and Incidence Of Thrombosis In Nephrotic Synmentioning
confidence: 99%
“…Such clinical manifestations may be even absent and the patients might be asymptomatic or with a subclinical course (13,17,18). …”
Section: Clinical Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation